Breslow Intermediates from a Thiazolin‐2‐ylidene and Fluorinated Aldehydes: XRD and Solution‐Phase NMR Spectroscopic Characterization. Issue 31 (5th July 2019) - Paul, Mathias; Neudörfl, Jörg‐M.; Berkessel, Albrecht
Abstract: The first generation and X‐ray diffraction (XRD) analysis of a crystalline Breslow intermediate (BI) derived from a thiazolin‐2‐ylidene, that is, the aromatic heterocycle present in vitamin B1, is reported. Key to success was the combined use of pentafluorobenzaldehyde and a thiazolin‐2‐ylidene carrying an enol‐stabilizing dispersion energy donor as N‐substituent. A so‐called primary intermediate (PI) could be isolated in protonated form (pPI) as well and analyzed by XRD. Furthermore, the first stable BI derived from an aromatic thiazolin‐2‐ylidene and an aliphatic aldehyde (trifluoroacetaldehyde) was prepared and characterized by NMR spectroscopy in solution. When switching to a saturated thiazolidin‐2‐ylidene, reaction with pentafluorobenzaldehyde afforded a new BI in solution (NMR spectroscopy). Attempts to crystallize the latter BI resulted in the isolation of a novel thiazolidin‐2‐ylidene dimer that had undergone rearrangement to a hexahydro[1, 4]‐thiazino[3, 2‐b]‐1, 4‐thiazine. Abstract : Back to nature : In vitamin B1 ‐catalyzed umpolung, a Breslow intermediate (BI) is formed from an aromatic thiazolin‐2‐ylidene and the substrate aldehyde. The combination of a N ‐Dipp‐substituted thiazolin‐2‐ylidene with pentafluorobenzaldehyde produced a BI, characterized by XRD. When trifluoroacetaldehyde was used, the first BI derived from a thiazolin‐2‐ylidene and an aliphatic aldehyde was generated, and characterized by NMR spectroscopy.